2015
DOI: 10.1007/s00204-015-1562-1
|View full text |Cite
|
Sign up to set email alerts
|

Combusting vegetable oils in diesel engines: the impact of unsaturated fatty acids on particle emissions and mutagenic effects of the exhaust

Abstract: High particle emissions and strong mutagenic effects were observed after combustion of vegetable oil in diesel engines. This study tested the hypothesis that these results are affected by the amount of unsaturated or polyunsaturated fatty acids of vegetable oils. Four different vegetable oils (coconut oil, CO; linseed oil, LO; palm tree oil, PO; and rapeseed oil, RO) and common diesel fuel (DF) were combusted in a heavy-duty diesel engine. The exhausts were investigated for particle emissions and mutagenic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Some reports showed that the diesel fuel (DF) is significantly higher when compared to BDF exhaust emission. On the other hand, BDF has shown a higher mutagenic potential in the Salmonella assay than DF in the some literatures [11][12].…”
Section: Introductionmentioning
confidence: 94%
“…Some reports showed that the diesel fuel (DF) is significantly higher when compared to BDF exhaust emission. On the other hand, BDF has shown a higher mutagenic potential in the Salmonella assay than DF in the some literatures [11][12].…”
Section: Introductionmentioning
confidence: 94%
“…In fact, the biological interactions of chemical components can also be antagonistic or synergistic. To fill the data gaps, Ames test [11] are routinely utilized to experimentally determine the genotoxicity of engine exhausts providing an overall genotoxicity of mixtures [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Coconut-biodiesel, a common biodiesel in Asia, is cost effective, has close properties to diesel and is globally available [63,64]. Combustion of coconut oil biodiesel has been shown to decrease CO, hydrocarbon content, polycyclic aromatic hydrocarbon (PAH) and decrease total PM from diesel emissions [63,65]. Another strategy to reduce diesel particulate matter is to use a fuel additive to improve the combustio n and energy efficiency of biodiesel [102].…”
Section: Discussionmentioning
confidence: 99%
“…Biodiesel and fuel additives are emerging interventions to address increasing fuel consumptio n, global warming and the adverse effect of fossil fuels [62]. Research has shown that coconut oil biodiesel can reduce mutagenicity of diesel emissions [65]. However, very little is known about the potential health effect of coconut oil biodiesel and triacetin as a fuel addictive to biodiesel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation